INSTITUTIONAL DESIGN AND CONSTITUTIONAL LEGITIMACY OF HUMAN RIGHTS SUPPORT INSTITUTIONS AFTER REFORMATION IN INDONESIA: DESAIN KELEMBAGAAN DAN LEGITIMASI KONSTITUSIONAL LEMBAGA PENUNJANG HAM PASCA REFORMASI DI INDONESIA - Eza Tri Yandy; Masburiyah; Tri Endah Karya Lestiyani; Sulaeman (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
The normative framework of Articles 28A–28J of the 1945 Constitution and Law No. 39 of 1999, as well as the establishment of independent institutions supporting human rights protection as a manifestation of the state's commitment to guaranteeing the constitutional rights of citizens and fulfilling its international obligations, marked a significant transformation of Indonesia's human rights protection system during the transition from the New Order regime to the Reform era. This research attempts to fill the gap in comprehensive analysis of the institutional legitimacy of human rights, the urgency of their establishment, and the problems in the implementation of their functions and authorities. Legal materials are examined both descriptively and qualitatively in this study, which employs a normative juridical method with a legislative, case, and conceptual approach. The study's findings indicate that while the normative and institutional framework for human rights protection has been comprehensively regulated, the implementation of these institutions' functions still faces three main problems: overlapping authority (for example, between the Attorney General’s Office and the National Commission on Human Rights in handling serious human rights cases), limited resources (budget and institutional capacity), and sociological aspects (low public awareness of the law). Therefore, there are three main aspects as recommendations from the institutional constraints faced, namely strengthening the regulatory framework of authority, establishing coordination mechanisms between institutions, and providing adequate institutional capacity support.